Predicting organizational citizenship behavior in a multicultural environment: The role of cultural intelligence and cultural distance - Kadam, Raavee; Balasubramanian, Sreejith; Kareem Abdul, Waheed; Jabeen, Shazi S (International journal of cross cultural management : CCM, 2021)
Cross-cultural research in organizational citizenship behavior (OCB) has primarily focused on testing the generalizability of various OCB dimensions in different cultures, while attempting to unearth any culture-specific OCB notions that may arise from the values of a particular culture. But with the contemporary workplace becoming increasingly multicultural, this research attempts to move beyond the study of OCB in culturally homogenous environments and investigates its manifestation in a multicultural context. This study proposes cultural intelligence (CQ) as one of the antecedents of OCB, which enables individuals in foreign cultures to understand the perceptions of OCB in that particular culture, and posits that individuals with high levels of CQ exhibit OCB in multicultural environments. Furthermore, this study investigates the moderating effect of cultural distance (CD) on the relationship between CQ and OCB to test whether culturally similar or different environments strengthen or weaken this relationship. The study draws upon the trait activation theory to test the hypotheses under investigation. Data for this study were collected from 513 expatriates of 31 different nationalities working in a multicultural environment and analyzed using structural equation modeling. The results indicated that CQ had a positive impact on OCB, but CD did not have any impact on the CQ-OCB relationship. The findings of this study have important implications for human resource managers managing a culturally diverse workforce.